Productive-Asset Zakat in Indonesia’s Political Economy: A Maqāṣid-Based Framework for Sustainable Empowerment - Bayu Arief Mahendra; Afrida Yanis; Bahruddin Zaini; Nor Salam; Ahsanul Mufid (Cv. Kayaswara, Indonesia, 2026)
This study employs a qualitative, descriptive-interpretive research approach to explore and understand how productive-asset zakat operates as an instrument of sustainable economic empowerment within the political economy of zakat governance in Indonesia. The research is motivated by the persistent gap between the normative ideal of zakat as a transformative welfare mechanism and its actual institutional implementation, particularly regarding the transition from consumptive distribution to productive-asset schemes, the regulatory centralisation that followed Law No. 23 of 2011, and the contested authority between the National Zakat Agency (BAZNAS) and private zakat institutions (LAZ). Data were collected through in-depth interviews with zakat managers (amil) and beneficiaries (mustahik), participant observation of empowerment programmes, and document analysis of regulations, annual reports, and programme records, with informants selected through purposive sampling. The analysis followed the Miles and Huberman interactive model of data condensation, data display, and conclusion drawing, with credibility ensured through source and method triangulation, member checking, and prolonged engagement. Findings are interpreted through a maqāṣid al-sharīʿah framework, which articulates the preservation of religion, life, intellect, lineage, and wealth (al-ḍarūriyyāt al-khams). The study finds that productive-asset zakat contributes positively to mustahik income, capability, and dignity, yet its optimal impact is constrained by asset-heavy disbursement detached from sustained mentoring, weak post-assistance monitoring, regulatory tension, and uneven institutional capacity. The study concludes that a maqāṣid-based framework reframes productive-asset zakat from short-term asset transfer toward sustainable empowerment, offering both a theoretical contribution to Islamic social finance and practical guidance for governance reform.